2019
DOI: 10.1016/j.ijscr.2019.10.036
|View full text |Cite
|
Sign up to set email alerts
|

A case of nodular fasciitis that was difficult to distinguish from sarcoma

Abstract: HighlightsNodular fasciitis is difficult to distinguish from sarcoma.Clinical and pathological findings may not correspond, as in our case.If sarcoma cannot be excluded, treatment should consider the risk of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
(25 reference statements)
1
20
0
Order By: Relevance
“…Plaza et al [13] reported that two thirds of their cases had been misdiagnosed as sarcoma. A different study showed a diagnostic dilemma when clinical findings suggestive of nodular fasciitis which turned out to be a peripheral nerve sheath tumor [14] . This case highlights the diagnostic dilemma encountered and the benefit of excisional biopsy and immunohistochemistry [15] in aiding our diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Plaza et al [13] reported that two thirds of their cases had been misdiagnosed as sarcoma. A different study showed a diagnostic dilemma when clinical findings suggestive of nodular fasciitis which turned out to be a peripheral nerve sheath tumor [14] . This case highlights the diagnostic dilemma encountered and the benefit of excisional biopsy and immunohistochemistry [15] in aiding our diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…NF may gradually disappear without surgical intervention. 17 Some studies [19][20][21] Compared with conventional skin imaging methods, with the ability of visualization of wholly morphological features, HR-MRI can easily show details of tumors simultaneously, which indicates its high clinical significance for the diagnosis of skin tumors. 22 Dynamic contrast-enhanced (DCE)-MRI can reflect perfusion and vascular permeability of living tissues based on the dynamic changes in signal intensity after contrast agent injection.…”
Section: Introductionmentioning
confidence: 99%
“…NF commonly appears rapid growth. The most common sites are the upper limbs [2], trunk [3], head [4] and neck [5]. Sometimes, such as salivary glands [6], breast [7], mesentery [8], and vulva [9] may be involved where were unusual locations.…”
Section: Introductionmentioning
confidence: 99%